Ethical Challenges in the Two Main Segments of the Insurance Industry: Key Considerations in the Evolving Financial Services Marketplace - Cooper, Robert W. (Journal of business ethics, 2002)
Based on the findings of several research studies of professionals in both the property-liability insurance industry and the life insurance industry, the paper makes and supports several important points. First, ethical challenges in the insurance industry involve not only a series of ethical dilemmas frequently faced by those working in the business, but also a variety of factors that hinder those working in the industry as they seek to resolve the ethical dilemmas encountered in the course of their work. Both of these two components of ethical challenges must be understood by those in the financial services industry who will deal with insurance operations in the future. Second, whereas the life insurance business and the property-liability insurance business have traditionally been viewed as being quite different from one another and still are in terms of operations and regulation, the research findings show that they are no longer very different in terms of the key ethical challenges faced by those working in the two segments of the industry. The paper shows how during the past decade the ethical challenges in the property-liability insurance industry have become quite similar to those in the more troubled life insurance industry.